2018
DOI: 10.1371/journal.pone.0193868
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic facial expressions of emotions are discriminated at birth

Abstract: The ability to discriminate between different facial expressions is fundamental since the first stages of postnatal life. The aim of this study is to investigate whether 2-days-old newborns are capable to discriminate facial expressions of emotions as they naturally take place in everyday interactions, that is in motion. When two dynamic displays depicting a happy and a disgusted facial expression were simultaneously presented (i.e., visual preference paradigm), newborns did not manifest any visual preference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 35 publications
2
37
0
1
Order By: Relevance
“…Moreover, it has been argued that early face-to-face interactions may form the basis of facial mimicry [13]. Although newborns can perceptually discriminate facial emotional expressions [14], the earliest evidence of emotional facial mimicry in infancy has been found around 5 months of age [15], but not earlier [16]. Importantly, scholars have described the function of mimicry as a “social glue” fostering liking, similarity and affiliation among social partners [1719] Indeed, facial mimicry of emotional expressions is thought to facilitate emotion recognition [20] and be related to empathy [21, 22].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been argued that early face-to-face interactions may form the basis of facial mimicry [13]. Although newborns can perceptually discriminate facial emotional expressions [14], the earliest evidence of emotional facial mimicry in infancy has been found around 5 months of age [15], but not earlier [16]. Importantly, scholars have described the function of mimicry as a “social glue” fostering liking, similarity and affiliation among social partners [1719] Indeed, facial mimicry of emotional expressions is thought to facilitate emotion recognition [20] and be related to empathy [21, 22].…”
Section: Introductionmentioning
confidence: 99%
“…From the first days of life, both infants and mothers contribute to these interactions (Lavelli & Fogel, 2005;Lavelli et al, 2019;Murray, 2014;Parsons et al, 2010). As seminal studies have shown, even newborns show a clear preference for faces (Bushnell, 2001;DeCasper & Fifer, 1980;Macfarlane, 1975;Turati et al, 2006), and the capacity both to express and discriminate different emotional expressions (Addabbo et al, 2018;Farroni et al, 2007). From 2 to 4 months of age, infants show sensitivity to variations in social and emotional stimulation (Cohn et al, 1990;Grossmann et al, 2008;Legerstee & Varghese, 2001;Murray & Trevarthen, 1985;Stormark & Braarud, 2004;Trevarthen, 2011), and can use communicative behaviors to maintain social contact and elicit re-engagement when it is temporarily lost (Bigelow et al, 2018;Bigelow & Walden, 2009).…”
Section: Early Mother-infant Interactionsmentioning
confidence: 99%
“…prediction about the face, jaw, eyes, mouth, and nose. One reason for doing this is to enable us to move away from end-to-end learning so as to improve performance by testing important feature groups as we know that certain emotional features are innately recognized [24].…”
Section: Context Phasementioning
confidence: 99%